Retrospective study of intellectual development in children treated for acute lymphoblastic leukaemia. Issue 7 (July 1977) - Eiser, C; Lansdown, R
Abstract : Nine younger children (mean age 6-3 years) and 6 older children (mean age 9-0 years), previously treated for acute lymphoblastic leukaemia by cranial irradiation and subsequently by 2 or 3 years of chemotherapy, were assessed in terms of intellectual development in relation to 15 controls, matched individually for age, sex, and social background. All children were functioning within a normal range. The older group of children performed as well as their matched controls in all tasks. However, the younger group tended to perform somewhat below their matched controls, and this applied especially to tasks measuring quantitative, memory, and motor skills, but not to language tasks. It is concluded that there is a continual need to monitor the development of children treated for leukaemia, especially when diagnosed in the 2- to 5- year age range.